2021
DOI: 10.1126/sciadv.abh2443
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid oxidation is a druggable gateway regulating cellular plasticity for driving metastasis in breast cancer

Abstract: Fatty acid oxidation is a metabolic gateway that regulates cellular plasticity and supports metastasis in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 79 publications
3
34
0
Order By: Relevance
“…Increasing reports demonstrated that FAO contributed to chemoresistance in gastric [ 28 ], breast [ 29 ], ovarian [ 30 ], and hepatocellular carcinomas [ 31 ]. Pharmacological inhibition of FAO sensitized leukemia cells to apoptosis [ 32 ], and synergetic of FAO inhibitors with Ara-C eradicated bone marrow resident chemoresistance AML cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing reports demonstrated that FAO contributed to chemoresistance in gastric [ 28 ], breast [ 29 ], ovarian [ 30 ], and hepatocellular carcinomas [ 31 ]. Pharmacological inhibition of FAO sensitized leukemia cells to apoptosis [ 32 ], and synergetic of FAO inhibitors with Ara-C eradicated bone marrow resident chemoresistance AML cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we performed a meta-analysis of oncovirus-positive samples in interconnected axes of cellular plasticity: EMT, metabolic reprogramming, and immune checkpoint expression (Dongre et al 2021; Jia et al 2021; Loo et al 2021; Lv et al 2021; Sahoo et al 2021). While crosstalk among these axes has been investigated in multiple cancers, their interconnection specifically in oncovirus-positive scenarios remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Acetyl-CoA levels have been previously linked to protein acetylation of Smad induced by leptin signaling 63 and histone acetylation 64-66 with subsequent breast cancer metastasis 63,64 . We add to this current knowledge by defining p65 as an acetylation target modulated by palmitate-derived acetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%